The experiences of preparation and engagement of educators in teaching e-portfolio - Fatemeh Keshmiri; Amir Houshang Mehrparvar (BMC Medical Education, 2023)
Abstract Introduction A teaching e-portfolio is used to organize the collation and presentation of documents about teaching for the development and evaluation of educators. The current study was aimed at describing teaching e-portfolio components at Shahid Sadoughi University of Medical Sciences. As well, we examined the performance and experience of educators in engaging in the teaching e-portfolio. Materials and methods This study was conducted at Shahid Sadoughi University in 2018–2022 in three main stages: (1) Development of the teaching e-portfolio; (2) Implementing teaching e-portfolio, and evaluating teaching documentation quantitatively; and (3) Exploration of educators’ experiences by a conventional content analysis introduced by Graneheim and Lundman. The teaching e-portfolio was developed from the perspective of the components, domains, and criteria of scholarship of teaching and learning. The teaching e-portfolio documented the educational activities of educators in 12 areas, including philosophy of education (1 activity), curriculum planning (4 activities), evaluation (7 activities), teaching and learning (1 activity), e-learning (1 activity), professional development in education (1 activity), scholarly activities (2 activities), mentoring and counseling (3 activities), educational leadership (2 activities), education research (6 activities), education reform project (1 activity), and production of scholarship of teaching and learning (13 activities). The educators recorded the documentation of educational activities in their teaching e-portfolio. Their documentation was reviewed by two peers. The reviewers delivered constructive feedback to improve the educators’ performance. The quantitative performance of educators in different activities in teaching e-portfolio was examined by descriptive tests (frequency and percentage). The experiences of educators were explored by the conventional content analysis approach which was introduced by Graneheim and Lundman. Results In the present study, 148 educators registered in the teaching e-portfolio. A total of 1488 documents of educational activities were registered in the e-portfolio from 2018 to 2022, and 55.24% of the activities received feedback in the peer review process. The experience of participants was categorized into a theme “fear and hope in utilizing teaching e-portfolio”. This theme consisted of three categories: “motivational roadmap for personal and professional development in the future”, “concern about the consequences of continuous monitoring”, and “restriction of resources and capability as resistance sources”. Conclusion The current study showed that the participation of educators in a teaching e-portfolio was at an acceptable level. Support systems and educational policies played an effective role in guiding educators to participate in educational development activities. The educators perceived the teaching e-portfolio as a two-faceted tool. Teaching e-portfolio can provide a road map for their personal and professional development to achieve excellent teaching. As well, the teaching e-portfolio was recognized as a tool for continuous performance monitoring and detection of the inefficiency of teaching quality activities. This perception, along with limited resources such as time, weak technological literacy, and difficulty in working with electronic devices and systems, led to resistance from educators to involve in teaching e-portfolio.